2016
DOI: 10.3727/096504016x14611963142218
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of PFTAIRE Protein Kinase 1 (PFTK1) Inhibits Proliferation, Invasion, and EMT in Colon Cancer Cells

Abstract: PFTK1 is a member of the cyclin-dependent kinase (CDK) family and is upregulated in many types of tumors. However, its expression and role in colon cancer remain unclear. In this study, we aimed to investigate the expression and function of PFTK1 in colon cancer. Our results showed that PFTK1 was highly expressed in colon cancer cell lines. The in vitro experiments demonstrated that knockdown of PFTK1 inhibited the proliferation, migration, and invasion of colon cancer cells as well as the epithelial-to-mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
3
14
0
1
Order By: Relevance
“…Based on all the researches and findings, we concluded that the Hh signaling pathway may play a crucial role in the tumorigenesis of CRCs 435,40,42,4749,53113. Although its exact role remains controversial, the expression of the Hh pathway in CRC tissues is much higher than in normal colon tissues, especially Shh and its signaling pathway components.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Based on all the researches and findings, we concluded that the Hh signaling pathway may play a crucial role in the tumorigenesis of CRCs 435,40,42,4749,53113. Although its exact role remains controversial, the expression of the Hh pathway in CRC tissues is much higher than in normal colon tissues, especially Shh and its signaling pathway components.…”
Section: Discussionmentioning
confidence: 92%
“…Shh is now considered to likely promote formation and metastasis of CRCs 24,35. It is believed that overexpression of Shh and its downstream components is highly correlated with the formation and metastasis of CRCs, whereas it’s detailed mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this opinion is a report that protein levels of sonic hedgehog signaling pathway components were elevated in melanosis coli, as in colorectal cancer [ 21 ]. Many evidences have demonstrated that sonic hedgehog signaling pathway was associated with development of CRC [ 22 24 ]. The pathogenesis of melanosis coli involves apoptosis of colonic epithelial cells caused by multiple toxic factors such as anthraquinone laxative abuse.…”
Section: Discussionmentioning
confidence: 99%
“…69 Studies have revealed that knockdown of CDK14 in cancer cells promoted E-cadherin expression, thus suppressing EMT. 44 , 47 , 70 However, the relationship between N-cadherin and CDK14 has not been fully elucidated. As miR-216a/CDK14 axis modulated OS tumour invasiveness, we thus sought to explore the effects of miR-216a/CDK14 axis on the E-cadherin and N-cadherin production in mice.…”
Section: Discussionmentioning
confidence: 99%